(3GdEaUGM Yf eYGfi GdUMGMs - (3jMji Hf (B((3gHjQI Hf(B) (3eMeO Hf gHjQI GdPgdj GdTjHGfqj, CHh GdeXaQ, Yhf GdOjf,J (B560 (3g` s
(3ChdgG (B:s
(3jHJOF HGdMOjK GdMGOi hGdSJjf Yf CHj gQjQI s
(3BNQgG (B:s
(3hjfJgi HGdMOjK GdNGeS hGdKdGKjf HYO GdeGFJjf Yf CHj gQjQI CjVkG s
(3LRA efg ef fSNI CNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B228s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B60 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B132s
(3eUOQ GbJfGA GdCUd (B:s
(3eOjfI (B(283) s
Keywords: (3GdMOjK h GdeUWdMs